Adolescent Reproductive Health Education Through Training and Counseling on Prevention of Free Relationships, LGBT and HIV AIDS at SMKN 3 Payakumbuh - Skunda Diliarosta Skunda Diliarosta (Fakultas MIPA Universitas Negeri Padang, 2020)
The purpose of this community service is to educate students in SMKN 3 Payakumbuh How to recognize and maintain reproductive health to avoid free sex, LGBT and HIV/AIDS. The education is well packed and interesting using animated films, discussing and solving problems as well as finding joint solution through a focus group discussion (FGD). This method is done so that students can easily understand about reproductive health and can find out the consequences of free and LGBT associations and HIV/AIDS disease. For initial analysis, this activity using Kahoot application with 75 questions. This activity is done with 5 stages, which is initiated by looking at the knowledge of students, introduce the reproduction tool, Issues of LGBT and Free Sex. Recognizing HIV/AID disease and sufferer data in West Sumatera. Then conducted group discussions with problem tree methods, Focused Group discussion (FGD), discussion of plenary and briefing from the resource person related to knowledge and action of reproductive health, free sex and LGBT. This activity has change attitude of SMKN3 PAYAKUMBUH students with a determination to reject the association/sex free and LGBT through the jargon